2011
DOI: 10.1590/s0102-05362011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Sweet pepper production in substrate in response to salinity, nutrient solution management and training system

Abstract: The objective of the present study was to evaluate the marketable fruit yield of sweet pepper plants (Capsicum annuum cv. Orlando) in function of the management of nutrient solution with training system. Plants were grown on coconut coir dust under greenhouse conditions in the southeast of Spain. A randomized block design in split-split plot with four blocks was used to test the effect of the nutrient solution strength (full or half-strength Hoagland nutrient solution), training system (two and three stems per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
(8 reference statements)
3
13
0
1
Order By: Relevance
“…The marketable fresh fruit yield with the use of saline water was 71% of the total fresh fruit yield, while it was 99% when non-saline water was used. The results obtained in this study are in close agreement with the report of Rubio et al (2011), who obtained marketable fruit yield of about 85% from the total fruit yield under non-saline conditions, whereas under saline conditions, it was between 55 and 76%. Also, previously, the reduction in marketable yield in pepper plants was mainly attributed to BER disease incidence (Silber et al, 2005) caused by increased salinity in the root medium (Rubio et al, 2009).…”
Section: Effect Of Irrigation Water Quality On Bell Pepper Fruit Yieldsupporting
confidence: 92%
See 2 more Smart Citations
“…The marketable fresh fruit yield with the use of saline water was 71% of the total fresh fruit yield, while it was 99% when non-saline water was used. The results obtained in this study are in close agreement with the report of Rubio et al (2011), who obtained marketable fruit yield of about 85% from the total fruit yield under non-saline conditions, whereas under saline conditions, it was between 55 and 76%. Also, previously, the reduction in marketable yield in pepper plants was mainly attributed to BER disease incidence (Silber et al, 2005) caused by increased salinity in the root medium (Rubio et al, 2009).…”
Section: Effect Of Irrigation Water Quality On Bell Pepper Fruit Yieldsupporting
confidence: 92%
“…Saline water use caused a greater reduction in the marketable fresh fruit yield (from 5.47 to 2.60 kg m -2 ) than the total fresh fruit yield (from 5.54 to 3.66 kg m -2 ). Similar results were reported by Rubio et al (2010;2011) who recorded lower marketable fruit yield from the saline water treatment (4.6 dS m -1 ) when compared to control (2.6 dS m -1 ). The lower fruit yield obtained by using saline water was mainly due to build up of soil Science Publications AJABS salinity, since water quality exhibited an overriding effect on soil Electrical Conductivity (EC).…”
Section: Effect Of Irrigation Water Quality On Bell Pepper Fruit Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies conducted by various authors have demonstrated that the reduction in fruit yield in bell pepper subjected to saline stress results from the decrease in the mean fruit weight and/or reduction in the number of fruits per plant (Arruda et al, 2011;Rubio et al, 2011;Rameshwaran et al, 2015), because fruits are the most sensitive organs to salinity (Azuma et al, 2010) due to the deleterious effects of saline stress on the increase of abortion rate, caused by the reduction in the number and viability of pollen grains (Ghanem et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Later he suggested that coir dust was renamed to cocopeat as this material has many characteristic of horticultural peat. This coconut coir dust or cocopeat is widely used for containerized growing medium for the production of ornamental potter plants (Bagci et al 2011;Scagel 2003;Tariq et al 2012) and other horticultural species (Ayesha et al 2011;Erwan et al 2013;Rubio et al 2011;Tehranifar et al 2007).…”
Section: Introductionmentioning
confidence: 99%